2020
DOI: 10.3389/fcell.2020.00255
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Spine and Synaptic Plasticity in Alzheimer’s Disease: A Focus on MicroRNA

Abstract: Dendrites and dendritic spines are dynamic structures with pivotal roles in brain connectivity and have been recognized as the locus of long-term synaptic plasticity related to cognitive processes such as learning and memory. In neurodegenerative diseases, the spine dynamic morphology alteration, such as shape and spine density, affects functional characteristics leading to synaptic dysfunction and cognitive impairment. Recent evidence implicates dendritic spine dysfunction as a critical feature in the pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 75 publications
0
43
0
Order By: Relevance
“…The dendritic spine number and shape affect synaptic plasticity, memory consolidation, and cognitive deficit in brain diseases 29 . To elucidate whether change in neurite complexity by metabolic imbalance and exendin-4 reflects alteration of dendritic spine morphology that indirectly represent synaptic plasticity and LTP in the mice brain, we examined the effect of exendin-4 on dendritic spine maturation in metabolic-imbalanced primary hippocampal and cortical neurons.…”
Section: Resultsmentioning
confidence: 99%
“…The dendritic spine number and shape affect synaptic plasticity, memory consolidation, and cognitive deficit in brain diseases 29 . To elucidate whether change in neurite complexity by metabolic imbalance and exendin-4 reflects alteration of dendritic spine morphology that indirectly represent synaptic plasticity and LTP in the mice brain, we examined the effect of exendin-4 on dendritic spine maturation in metabolic-imbalanced primary hippocampal and cortical neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Targeting synaptic deficits in AD patients and aging individuals by improving synaptic plasticity though alteration of structural deficits in dendritic spines through microRNA mediated regulatory pathways could be an effective and novel therapeutic strategy for AD as well as other neurodegenerative disorders [126].…”
Section: Author Detailsmentioning
confidence: 99%
“…It has been reported that the dendritic spine's number and shape affect synaptic plasticity, memory consolidation, and cognitive deficit in brain diseases 23 . To further elucidate whether the changes of neurite formation and complexity by metabolic imbalances and exendin-4 reflect the alteration of dendritic spine morphology that indirectly represent synaptic plasticity and LTP in the mice brain, we tried to examine the dendritic spine maturation in neurons under the metabolic imbalance condition.…”
Section: Exendin-4 Improved Neuronal Dendrite Outgrowth and Dendriticmentioning
confidence: 99%